Popper's Open society after fifty years : the continuing relevance of Karl Popper - Jarvie, I. C. (Ian Charles), 1937-; Pralong, Sandra, 1958- (Routledge, 1999)
Popper's Open Society After Fifty Years presents a coherent survey of the reception and influence of Karl Popper's masterpiece The Open Society and its Enemies over the fifty years since its publication in 1945, as well as applying some of its principles to the context of modern Eastern Europe. This unique volume contains papers by many of Popper's contemporaries and friends, including such luminaries as Ernst Gombrich, in his paper 'The Open Society and its Enemies: Remembering its Publication Fifty Years Ago'.